Performance-Focused Human Resource Development In IT Consulting Firms - Umi Kulsum; Titin Ruliana; Nurfitriani Nurfitriani; Heriyanto Heriyanto (International Journal of Management Research and Economics, 2025)
Performance-focused human resource development in IT consulting firms. The purpose of implementing this program is to find out the management of human resources that occurs in the company, how companies manage human resources so that performance i mprovements can occur in IT consulting companies and what efforts have been made by companies to manage their companies that have an impact on improving performance as well as what assessment methods used by companies to measure employee performance. Problems that arise such as excessive working hours and other problems can be found in this new start-up company. The method used in this activity is online (using the Zoom us application, Google Meet) and face-to-face. The results of the research conducted indicate that employee performance is very good, companies can find solutions to their employee performance problems by providing some training, mentoring to bonuses that can increase motivation so that employee performance can increase and have a good influence on employees. The company uses the graph rating scale method and the alternative ranking method, where the employee who gets the top rank will be given an annual bonus by the company.